Violência escolar entre alunos do ensino médio integrado: uma análise a partir do Instituto Federal do Ceará-Campus Iguatu - Barros, Maria Maiza (2015)
This research investigated school violence among the integrated high school students of the Federal Institute of Ceará Iguatu Campus. It is a qualitative and quantitative research about the history of the culture of violence in the school, the main types of violence, the characteristics of the aggressors, the victims and the witnesses, differences in the forms of violence among the students and the current legislation on the theme. The analyses of the questionnaires applied to the students showed that: the violence among the students is present in both sexes, with the predominance being in the masculine sex, and is in all ages and grades of the integrated high school and in the three enrollment regimes and manifests itself in the forms of verbal, physical, virtual, psychological, sexual, bullying and practical joke violence. The results showed that: the violence among the students has always been present and has been perpetuated throughout the years presenting itself in various types of violence, being that the practical jokes and the power relations between students of different grades has already become culture in the institution. It was also observed that the existing legislation does not contemplate certain forms of violence found in the school environment, indicating a need for adjustment in order to inhibit these forms of violence. We dealt with the current legislations on the theme, beginning with the broadest law going to the most specific which is the internal regulations of the institution.